ON (N (k), ξ)-SEMI-RIEMANNIAN 3-MANIFOLDS - Prakasha, D.G.; Nagaraja, H.G.; Somashekhara, G. (Italian Journal of Pure and Applied Mathematics, 2014)
The object of the present paper is to study 3-dimensional (N (k), ξ)-semi-Riemannian manifolds. We study (N (k), ξ)-semi-Riemannian 3-manifolds which are Ricci-semi-symmetric, locally ϕ-symmetric and have η-parallel Ricci tensor.